PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PT. NAWASENA PUTRA WINDU) - Muhammad Kevin Aribi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Nawasena Putra Windu is engaged in the supplier industry of several large trade products such as fertilizers, stationery, textiles, laboratory equipment, and even oil palm fruit plantations. The purpose of this study is to find out how and how much leadership style and work motivation influence employee performance. This study uses a statistical quantitative method processed through SPSS version 21. The t-test produced a leadership style (X1) that did not have a significant effect on employee performance partially because it made a tcal value of 0.478 < 2.039 and a substantial value of 0.636 > 0.05 so that Ha1 was rejected, work motivation (X2) had a significant effect on employee performance partially because it produced a tcal value of 9.793 > 2.039 and a significance value of 0.000 < 0.05 so that Ha1 was accepted. However, the f-test produced a positive and significant effect on employee performance simultaneously. It made a Fcal of 82,009 > a table of 3.30 and a significance value of 0.000 < 0.05 so Ha3 was accepted. Therefore, if the leadership style and work motivation improve, the performance of employees will also be better.